2021
DOI: 10.3389/fnut.2021.735501
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Anoectochilus roxburghii Polysaccharide and Exercise Ameliorates Diet-Induced Metabolic Disorders in Obese Mice

Abstract: Metabolic syndrome is a cluster of metabolic disorders that threatens public health. Nevertheless, its exact mechanism and relative intervention remain largely obscure. Accumulating evidence indicate that tither Anoectochilus roxburghii polysaccharide (ARP) or exercise (EX) exhibited the beneficial effects on metabolic health. However, the synergetic beneficial effects of ARP and EX as a combined intervention on obesity-induced metabolic disorders remain largely obscure. Male C57BL/6 mice were fed a high-fat d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…All mice had freely access to food and drink for 12 weeks. The exercise training followed a previous report 46 . In brief, for the first 4 weeks, the mice in the exercise group got a mild intensity run on treadmill with 5 m/min for first 5 min, 10 m/min for the subsequent 30 min, and 5 m/min for the final 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All mice had freely access to food and drink for 12 weeks. The exercise training followed a previous report 46 . In brief, for the first 4 weeks, the mice in the exercise group got a mild intensity run on treadmill with 5 m/min for first 5 min, 10 m/min for the subsequent 30 min, and 5 m/min for the final 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The exercise training followed a previous report. 46 In brief, for the first 4 weeks, the mice in the exercise group got a mild intensity run on treadmill with 5 m/min for first 5 min, 10 m/min for the subsequent 30 min, and 5 m/min for the final 5 min. For the last 8 weeks, the mice in the exercise group had a moderate intensity on treadmill with 5 m/min for the first 5 min, 13 m/min for the subsequent 30 min, and 5 m/min for the final 5 min.…”
Section: Animalsmentioning
confidence: 99%
“…Animal experiments have indicated that NPs from woody plants could regulate Nrf2 antioxidant pathway for liver protection ( 30 , 50 , 79 , 80 , 82 , 83 , 87 , 88 , 90 , 91 , 94 , 172 , 176 ), cardioprotection ( 77 ), anti-aging ( 74 , 76 ), anti-oxidation ( 177 179 ), and immunomodulation ( 180 , 181 ), as reflected in Table 2 .…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
“…NPs from woody plants had liver protection against H 2 O 2 -induced hybrid grouper ( 30 ), acetaminophen-induced mice ( 50 , 82 , 87 ), high-fat diet-induced mice ( 79 , 94 , 176 ), CCl 4 -induced mice ( 80 , 90 ), ethanol-induced mice ( 87 , 88 ), and concanavalin A-induced mice ( 83 ), involving with increment of protein and/or mRNA expressions of nuclear Nrf2, Nrf2, HO-1, NQO1, GCLC, CAT, GSTα, GPX, GR, and MKP1 along with nuclear translocation of Nrf2, and reduction of protein and/or mRNA expressions of Keap1 and cytosol Nrf2 in liver tissues. Fructus Aurantii polysaccharide exerted cardioprotection against isoproterenol-induced rats via enhancing protein expressions of HO-1, NQO1, GCLM, γ-GCS, nuclear Nrf2, and cytosol Nrf2 in cardiac muscle tissues ( 77 ).…”
Section: Regulation Of Nps On Nrf2 Antioxidant Pathway For Health-pro...mentioning
confidence: 99%
“…Moreover, the mitochondrial complex and PGC-1α were activated to promote mitochondrial function. Furthermore, ARP also had some effects on reducing ROS levels and increasing ATP levels, thereby significantly improving diet-induced OS ( Chen et al, 2021 ).…”
Section: Application Of Natural Polysaccharides In Treating Diabetes ...mentioning
confidence: 99%